2019
DOI: 10.3389/fpsyg.2019.00820
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Wellbeing Among College Music Students and Amateur Musicians in Western Switzerland

Abstract: Musical performance requires the ability to master a complex integration of highly specialized motor, cognitive, and perceptual skills developed over years of practice. It often means also being able to deal with considerable pressure within dynamic environments. Consequently, many musicians suffer from health-related problems and report a large number of physical and psychological complaints. Our research aimed to evaluate and analyze the wellbeing of two distinct groups of musicians, college music students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 90 publications
(115 reference statements)
0
21
1
1
Order By: Relevance
“…The Cronbach's alpha coefficient reported for the WHO-5 is >0.80 (e.g., Garland et al, 2018;Ismail et al, 2018). Whilst the WHOQOL-BREF (1998) has previously been used in studies of music students (Philippe et al, 2019) and sport (Verkooijen et al, 2012;Yazicioglu et al, 2012), to the best of our knowledge, this very short version has not.…”
Section: Wellbeing Measuresmentioning
confidence: 89%
See 2 more Smart Citations
“…The Cronbach's alpha coefficient reported for the WHO-5 is >0.80 (e.g., Garland et al, 2018;Ismail et al, 2018). Whilst the WHOQOL-BREF (1998) has previously been used in studies of music students (Philippe et al, 2019) and sport (Verkooijen et al, 2012;Yazicioglu et al, 2012), to the best of our knowledge, this very short version has not.…”
Section: Wellbeing Measuresmentioning
confidence: 89%
“…In the present study, we focus on the health and wellbeing of students in 'performance-orientated' vocation-based subjects, such as sport and music students, in which there is an embodied element of expertise in comparison to general university courses (i.e., other students). This is because research has suggested that the nature of demands involved in 'performance-orientated' and embodied areas of study, like music and sport, may paradoxically enhance wellbeing (e.g., Malebo et al, 2007;Ascenso et al, 2018a,b;Philippe et al, 2019), and/or be detrimental to physical and mental health (e.g., Bartholomew et al, 2011;Hildebrandt et al, 2012;Spahn et al, 2017;Kouali et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such efforts to develop greater engagement have been found by McPherson et al (2012) to increase practice efficiency. In addition, accompanying music students in the development of self-regulated skills to prepare for exams or recitals could help them experience these events in a more serene way and thus improve their general well-being and health (Williamon and Thompson, 2006;Kreutz et al, 2009;Antonini Philippe et al, 2019).…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%
“…Recently, studies have focused on a more positive psychological approach to performance in order to encourage and reinforce health-promoting behaviors in conservatoires and schools of music (see Ascenso et al, 2017Ascenso et al, , 2018Perkins et al, 2017). One study (Antonini Philippe et al, 2019) revealed that, for those students who commit to music professionally, more action is needed to support their health directly and to bolster the value placed on health, both by the musicians themselves as well as their teachers, administrators, and support staff. The results also highlight exciting new possibilities for intervention programs aimed at assisting musicians in drawing closer ties between improving health and enhancing performance, many of which have already been piloted and applied in sporting contexts (see Williamon et al, 2017).…”
Section: Lessons Learned From Sports: Perspectives On Advancing Perfomentioning
confidence: 99%